Antigen/IgG immune complex-primed mucosal mast cells mediate antigen-specific activation of co-cultured T cells - Ding, Jie (Immunology, 2015)
Mast cells are proposed to be one of the targets for mucosal vaccine adjuvants. We previously demonstrated that mucosal adjuvants containing IgG immune complexes could activate connective tissue mast cells enhancing immune responses. Here we suggest that mucosal mast cells (MMC) may also contribute to augmentation of antigen-specific immune responses following treatment with antigens complexed with IgG. We demonstrated that both bone marrow-derived cultured MMC and tissue resident MMC incorporated ovalbumin (OVA) at a greater level in the presence of anti-OVA IgG. Co-culture of OVA/IgG-pulsed bone marrow-derived MMC with splenocytes from OT-II mice promoted OVA-specific activation and proliferation of T cells, a process known as cross-presentation. Furthermore, bone marrow-derived cultured MMC underwent apoptosis following treatment with IgG immune complexes, a feature that has been described as favouring phagocytosis of mast cells by professional antigen-presenting cells.